Proximate and physicochemical analysis of pink guava juice fortified with vitamin e / Mohamad Shahrimi Hashim and Faikah Awang @ Ismail - Hashim, Mohamad Shahrimi; Awang @ Ismail, Faikah (Universiti Teknologi MARA, Negeri Sembilan, 2021)
This study is focused on determination of proximate and physicochemical properties of pink guava juice (PGJ) fortified with vitamin E. Coffee, tea, or carbonated soft drinks are popular however the customer nowadays is more health conscious and start reducing caffeine-containing beverages from daily intake and replacing it with fruit juices such as PGJ. In addition, beverages with added value such as vitamin E that are highly demanded in the fruit juice market globally. The experimental work of this research are proximate analysis (i.e. protein, carbohydrate, fat, fibre, ash and moisture content) followed by physico-chemical properties (i.e titratable acidity, pH, total soluble solid (TSS), water activity (aw), viscosity determination and colour analysis (i.e. lightness (L*), chroma (C*) and hue angle (Ho)). Results showed that pink guava juice (PGJ) contained protein (0.67 ± 0.15a %), carbohydrate (4.96 ± 0.59a % ), fat (0.27 ± 0.05a % ), total fiber (0.74 ± 0.10a % ), ash (0.64 ± 0.10a % ), moisture (92.72 ± 0.91 a % ), acidity (0.41 ± 0.10 a %), pH (3.65 ± 0.12a), TSS (10.56 ± 0.43a), aw (0.99 ± 0.02a), viscosity (15.33 ± 1.15a mPa.s), L* (31.95 ± 0.02a), C* (34.65 ± 0.01a), Ho (25.42 ± 0.02a) and vitamin E content (17.44 ± 1.63a mg/l). In conclusion, this study will be useful for preliminary information regarding pink guava juice and also Vitamin E-Fortification for fruit juice in the future.